55 ESTROGEN INHIBITS TUMOR NECROSIS FACTOR α-INDUCED EXPRESSION OF INFLAMMATORY MEDIATORS IN RAT AORTIC SMOOTH MUSCLE CELLS IN VITRO. (1st January 2005) - Feng, W.; Xing, D.; Chen, Y. F.; Oparil, S.
Abstract : Introduction: We have previously shown that estrogen (17β-estradiol, E2) attenuates neointima formation in response to balloon injury of the rat carotid artery in vivo, in part by decreasing expression of pro-inflammatory mediators and migration of neutrophils and monocytes/macrophages into injured vessels. This study tested the hypothesis that activated rat aortic smooth muscle cells (RASMC) express adhesion molecules, chemokines and cytokines that recruit leukocytes and promote inflammation, and that E2 inhibits expression of these mediators. Methods: Quiescent cultured RASMCs were pretreated with E2 or vehicle for 24 hrs before tumor necrosis factor (TNF)-α (0.1-1.0 ng/mL) was added. Cells were harvested 6 hrs later. SYBR green real-time RT-PCR was used to detect mRNA expression of chemokines cytokine-induced neutrophil chemoattractant (CINC)-2, monocyte chemoattractant protein (MCP)-1, cytokine interleukin (IL)-6, intercellular adhesion molecule (ICAM)-1, vascular cell adhesion molecule (VCAM)-1 and other pro-inflammatory mediators cyclooxygenase (COX)-2, transforming growth factor (TGF)-β in these RASMCs. Results: Data are normalized to the mean mRNA level of vehicle treated RASMCs except for CINC-2 and MCP-1, which were undetectable (UD) in the vehicle group. E2 significantly reduced TNF-α-stimulated expression of CINC-2, MCP-1, IL-6, ICAM-1, VCAM-1 and COX-2. Expression of TGF-β was not increased by TNF-α or altered by E2 treatment. Conclusion: Activated (by TNF-α) RASMCs exhibit robust expression of proinflammatory mediators in vitro that is inhibited by E2. Coupled with our previous in vivo observations, these findings suggest that this anti-inflammatory effect contributes to E2-induced vasoprotection in the setting of acute injury and that SMCs may be a target cell for E2 in this setting. (table )